Third International Conference on Applications of Optics and Photonics 2017
DOI: 10.1117/12.2270880
|View full text |Cite
|
Sign up to set email alerts
|

Optical microtopographic inspection of asphalt pavement surfaces

Abstract: Microtopographic and rugometric characterization of surfaces is routinely and effectively performed non-invasively by a number of different optical methods. Rough surfaces are also inspected using optical profilometers and microtopographer. The characterization of road asphalt pavement surfaces produced in different ways and compositions is fundamental for economical and safety reasons. Having complex structures, including topographically with different ranges of form error and roughness, the inspection of asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, there are a few types of equipment, such as the optical triangulation based-microtopographer, capable of doing it in asphalt mixtures (Costa, 2012). Previous work carried out with this equipment showed that the amplitude parameters Sa, Sq and Total Height of the Surface (St) are not directly affected by the type of bitumen (Costa, Freitas, Torres, & Cerezo, 2017).…”
Section: S579mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are a few types of equipment, such as the optical triangulation based-microtopographer, capable of doing it in asphalt mixtures (Costa, 2012). Previous work carried out with this equipment showed that the amplitude parameters Sa, Sq and Total Height of the Surface (St) are not directly affected by the type of bitumen (Costa, Freitas, Torres, & Cerezo, 2017).…”
Section: S579mentioning
confidence: 99%
“…To measure the microtexture, an optical microtopographer was used. With large measuring range, high versatility, robustness and reliability, good accuracy and resolution, the MICRO-TOP.06.MFC microtopographer (Figure 1) was used to inspect a wide range of surface types (Costa, 2012), including asphalt mixtures (Costa et al, 2017). The system is based on discreet active triangulation.…”
Section: Microtexturementioning
confidence: 99%